Off-balance-sheet equity: The engine for energy efficiency capital mobilization - Alexander Ablaza; Yang Liu; Mikhael Fiorello Llado (Asian Development Bank Institute (ADBI), 2020)
The International Energy Agency estimates that 24.5 trillion of energy efficiency (EE) investments will be needed through 2040. Debt- and self-financed projects are expected to contribute only a third of this capital due to multiple barriers. On the one hand, self-financed projects require upfront capital from companies' budgets to be spent on EE, which most would regard as a noncore activity. On the other hand, multiple parties face hurdles in a debt-financed project: 1) banks deem EE transactions too small and risky; and 2) most energy service companies (ESCOs) do not have creditworthy balance sheets. Leasing agreements also have unattractive rates and extract too much project value from ESCOs and/or end users. Altogether, these constraints call for nonmainstream, off-balance sheet financial structures that will shift project risks to third parties and facilitate market benefits, such as collateralization of energy savings and engagement of SMEs. Such structures include ESCO performance contracts, public-private partnership transactions, ESCO guarantee funds, super ESCOs, and other equity channels. These financing modalities require development in both the ESCO/EPC sector and EE policies, which could effectively mobilize and de-risk significant capital volumes.
Keywords: Q40; Q42; Q48; 330; energy efficiency capital; energy efficiency finance; energy performance contracting (EPC); energy service company (ESCO); equity finance; off-balance sheet finance